Keabsahan Akta Notaris yang Tidak Dibacakan Dihadapan Para Penghadap dan Saksi - Agung, Stefanus; Darmadi, Anak Agung Ngurah Oka Yudistira (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p5, 2024)
The aim of this written document is to assess the legitimacy of a Notarial deed that hasn't been read aloud to the involved parties and witnesses. In this study, normative research methods are employed for analysis, utilizing the approach of legislation and a concept analysis., remains guided by primary and secondary legal sources. According to the research findings, when a notary deed isn't read aloud to the involved parties and witnesses, it becomes invalid due to non-compliance with legal provisions. Consequently, the deed loses its validity and does not hold full legal force, resembling the status of a private deed.